1982
DOI: 10.7326/0003-4819-96-6-865
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Neuropsychological Sequelae of Toxic Shock Syndrome

Abstract: Twelve women, aged 16 to 29 years, were interviewed and examined for possible neuropsychological sequelae 2 to 12 months after they recovered from toxic shock syndrome. Six of the 12 women had symptoms such as difficulty concentrating, headache, recent memory lapses, inability to compute, and loss of other higher integrative functions. Eight patients were found to have electroencephalographic abnormalities. All six symptomatic patients but no asymptomatic patients had abnormal neurologic findings. Abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Ely and coworkers [2] found that 18.5% of 275 mechanically ventilated patients had persistent coma, and of the remaining patients 81.7% developed delirium. Similar findings have been reported by other investigators [3-6]. The delirium tends to involve bizarre and terrifying nightmares, hallucinations, and paranoid delusions – often of the clinical staff trying to rape, murder, or otherwise harm the patient [7,8].…”
Section: Measuring Cognitive Impairment: Intensive Care Unit Deliriumsupporting
confidence: 83%
“…Ely and coworkers [2] found that 18.5% of 275 mechanically ventilated patients had persistent coma, and of the remaining patients 81.7% developed delirium. Similar findings have been reported by other investigators [3-6]. The delirium tends to involve bizarre and terrifying nightmares, hallucinations, and paranoid delusions – often of the clinical staff trying to rape, murder, or otherwise harm the patient [7,8].…”
Section: Measuring Cognitive Impairment: Intensive Care Unit Deliriumsupporting
confidence: 83%
“…In 1986, the overall case fatality rate was estimated to be 4%, with young women as the highest risk group (median age, 25 years) [9]. In the early 1980s long-term morbidity was observed in up to 90% of TSS cases, with 20% experiencing recurrent episodes, 50% having long-term memory loss and abnormal EEG findings, and 23% having recurrent syncope or cardiomyopathy [10][11]. Since 1986, there has not been population-based active surveillance to assess the incidence or disease burden of TSS.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired mem ory and poorly sustained concentration have been described in patients who required only intravenous fluids to restore blood pressure (67). These findings lead to speculation that the TSS-associated toxin(s) may have a direct effect on nerve or muscle tissue.…”
Section: Outcomementioning
confidence: 95%